The teaching of religious moderation in fikih through group discussions at binbaz yogyakarta - Muhammad Chafidz Ali Wafa; Wahyudin Hafiz; Muhamad Tamam Basith; Rio Bastian (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
Salafiyah Wustho Islamic Center Bin Baz is a school equivalent to junior high school. Salafiyah Wustho has various problems that are often faced by teachers in the Fiqh learning process, such as students not paying attention during learning, to students' lack of ability to understand the lesson and express opinions about the material presented. This affects student learning outcomes which then become academic records which then become evaluation material. In this case, the teacher tries to contribute to making improvements related to student learning outcomes by using the group discussion method. This research is field research. This research uses qualitative methods, meaning the results were not obtained through statistical techniques or other calculations. Qualitative research, also known as naturalistic research, conducts research in a natural environment, or natural setting, without converting it into numbers or symbols. The results of this research are an increase in the learning outcomes of class VIII A students in the Fiqh subject. This is proven by the pre-test results, the average value of which is still much below the KKM and the post-test scores which have increased significantly, because there has been an increase from pre-test to post-test. In implementing this group discussion method, there are several inhibiting factors, namely lack of time, the learning method used is still conventional, therefore causing students' concentration to decrease due to boredom while learning is taking place. The supporting factors in implementing this group discussion method are that students are very enthusiastic and the class is more conducive because there is strong motivation from the students so that students are very enthusiastic about participating in learning using the group discussion method.